Sleep and chronotype in university students in COVID-19 pandemic (Research, Society and Development, 2020)
Introduction: In order to perform its specific functions (e.g., hormone production, cellular homeostasis and immunology), it is essential that the hours of sleep are correct. However, this quantity and quality of sleep can be impaired by several factors, such as psychological and environmental. Therefore, the objective was to investigate in the literature the sleep habits, chronotype and biological clock of university students in the current pandemic scenario of COVID-19. Methodology: A narrative bibliographic review was carried out with scientific articles published between 2010 and 2020 in the Cochrane, Embase, Web of Science, LILACS, Scielo, Pubmed, Sciencedirect databases; the descriptors were "sleep", "sleep disorders", "chronotype", "biological clock", "circadian rhythm", "morning", "evening", "students", "university students", "epidemics", "pandemics" , “COVID-19” and the Boolean “and”. Results and discussion: Making up the interactive complexity of sleep with the biological clock, are fluctuations, sensitivity, homeostasis, photopic and seasonal influence, pathology, body temperature, food, hormonal levels, immune system, psychological changes and physical activity. Consequently, many aspects related to the chronotype of young university students were altered and with prejudice to it, especially in view of the current stressful situation, which is the COVID-19 pandemic. Conclusion: Sleep and chronotype exert various physiological processes on the body of university students. This occurs in a non-linear and quite complex way; levels of cortisol, growth hormone, melatonin and fluctuations in body temperature were shown to be predictive and sensitive to changes in the sleep-wake process.